Comparison of SARS-CoV-2 spike-specific IgA and IgG in nasal secretions, saliva and serum - Bladh, Oscar; Aguilera, Katherina; Marking, Ulrika; Kihlgren, Martha; Greilert Norin, Nina; Smed-Sörensen, Anna; Sällberg Chen, Margaret; Klingström, Jonas; Blom, Kim; Russell, Michael W.; Havervall, Sebastian; Thålin, Charlotte; et al. (Frontiers in Immunology, 2024)
Several novel vaccine platforms aim at mucosal immunity in the respiratory tract to block SARS-CoV-2 transmission. Standardized methods for mucosal sample collection and quantification of mucosal antibodies are therefore urgently needed for harmonized comparisons and interpretations across mucosal vaccine trials and real-world data.Using commercial electrochemiluminescence antibody panels, we compared SARS-CoV-2 spike-specific IgA and IgG in paired saliva, nasal secretions, and serum from 1048 healthcare workers with and without prior infection.Spike-specific IgA correlated well in nasal secretions and saliva (r>0.65, p<0.0001), but the levels were more than three-fold higher in nasal secretions as compared to in saliva (p<0.01).Correlations between the total population of spike-specific IgA and spike-specific secretory IgA (sIgA) were significantly stronger (p<0.0001) in nasal secretions (r=0.96, p<0.0001) as opposed to in saliva (r=0.77, p<0.0001), and spike-specific IgA correlated stronger (p<0.0001) between serum and saliva (r=0.73, p<0.001) as opposed to between serum and nasal secretions (r=0.54, p<0.001), suggesting transudation of monomeric spike-specific IgA from the circulation to saliva. Notably, spike-specific sIgA had a markedly higher SARS-CoV-2 variant cross-binding capacity as compared to the total population of IgA and IgG in both nasal secretions, saliva and serum, (all p<0.0001), which emphasizes the importance of taking potential serum-derived monomeric IgA into consideration when investigating mucosal immune responses.Taken together, although spike-specific IgA can be reliably measured in both nasal secretions and saliva, our findings imply an advantage of higher levels and likely also a larger proportion of sIgA in nasal secretions as opposed to in saliva. We further corroborate the superior variant cross-binding capacity of sIgA in mucosal secretions, highlighting the potential protective benefits of a vaccine targeting the upper respiratory tract.